IMAM TIRMIDHI'S CONTRIBUTION TO THE SCIENCE OF HADITH - Hamzayev Ali Abbos o'gli (Journal Park Publishing, 2023)
The article describes Imam Tirmidhi's life, works, scientific journeys and the recognition of his teachers. Six books are recognized in the science of Hadith and they are known as "Kutubi sitta" ("Six books"). Among these books, the importance of "Sunani Tirmidhi" is mentioned.
Keywords: Imam Tirmidhi, Sunani Tirmidhi, hadith, Imam Bukhari, The Holy Quran, manners.